The effect of ethical orientation and moral intensity on future auditors' ethical judgment / Razana Juhaida Johari, Noraida Saidi and Wan Fairos Wan Yaacob - Johari, Razana Juhaida; Saidi, Noraida; Wan Yaacob, Wan Fairos (2014)
Several highly publicized financial disasters in the past decade have brought into question the auditors' integrity and credibility especially related to their ethical behavior (Kung & Huang, 2013). More specifically, misconduct of auditors, has drawn significant attention to the importance of ethics and integrity in public accounting. As a result, accounting firms have taken actions to reestablish credibility within the profession. The overall goal of these incentives is to provide ethics education to the auditors. and recognize auditors who have demonstrated outstanding commitment to ethics in the marketplace (KPMG International, 2012). However, in the wake of the aforementioned accounting scandals, many authors have argued that ethics education should start early in an auditors career, even before joining the profession (Suryaningrum et al., 2013). Noting the importance of moral intensity construct and ethical orientation dimensions in shaping the auditors ethical judgment, this current study provides further evidence by investigating these two variables on future auditors' ethical judgment. The Structural Equation Modeling (SEM) technique is used in analyzing the data that was collected through the questionnaire design. The findings of this study could contribute to the existing literature on ethics within the academic curriculum and, in particular, offer an insight on accounting ethics in Malaysia.